Restorative Justice in Children's Criminal Jurisdiction System through Diversion - Nur Indah Setyoningrum; Anis Mashdurohatun (Law Development Journal, 2021)
Diversion is a constructive effort to rebuild social relations that have been damaged by criminal acts, basically diversion has relevance to the purpose of punishment for children. The formulation of the problem is 1) How is the implementation of restorative justice in the Juvenile Criminal Justice System through diversion at the Semarang City District Attorney, 2) What are the obstacles in the implementation of restorative justice in the Juvenile Criminal Justice System through diversion at the Semarang City District Attorney. The method used is juridical empirical. The results of this study are: 1) This is due to the need for time to adjust to the new regulations in effect, in order to meet the completeness of supporting infrastructure and equitable distribution of trained and reliable human resources in every judicial institution in various regions throughout Indonesia, especially those dealing with child crimes. 2) The child protection system is not working in every case of children who are in conflict with the law